Prevalence and Etiology of Neonatal Jaundice in a Tertiary Care Hospital - Acharya, Niraj; Paneru, Chandra Prasad (Journal of Nepalgunj Medical College, 2021)
Introduction: Neonatal jaundice is a major clinical condition worldwide occurring in upto 60% of term and 80% preterm newborn in the first week of life. Neonatal jaundice is defined as total serum bilirubin level above 7 mg/dl. Aims: This study was done to find out the prevalence and etiology of neonatal jaundice in neonates admitted to Neonatal Intensive Care Unit (NICU) of Nepalgunj Medical College Teaching Hospital (NGMCTH) Kohalpur, Banke. Methods: It was a prospective cross sectional hospital based study conducted from November 2018 to November 2019 in Neonatal Intensive Care Unit of Nepalgunj Medical College Teaching Hospital. All neonates with clinical jaundice and hyperbilirubinemia with total serum bilirubin of ≥7 mg/dl were subjected to complete history taking, through physical examination and investigations. Results: Out of 892 neonates who developed clinical jaundice, 640 neonates whose parents gave consent were included in the study. The prevalence of neonatal jaundice was found to be 39.85% with male to female ratio of 1.79:1. In the present study pathological jaundice was seen in 74.94% whereas physiological jaundice in 23.66%. Among the various etiologies of pathological jaundice, neonatal sepsis (44.52%) was found to be the most common cause followed by ABO incompatibility (12.18%) and Rh incompatibility (7.03%). Conclusion: The prevalence of neonatal jaundice in present study was 39.85% and the most common cause was neonatal sepsis .The prevalence of jaundice was more in preterm than in term neonates. Neonatal jaundice is very common morbidity in NICU especially in preterm babies.